Hubungan Antara Dukungan Orang Tua Dengan Kecenderungan Perilaku Seksual Pada Remaja Wilayah Bekasi Utara - Amelia, Ananda Puteri; Muzzamil, Ferdy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Relationship Between Parental Support and Sexual Behavior Trends in Adolescents in North Bekasi. This study aims to find out whether there is a relationship between parental support and sexual behavior in adolescents. The research method used is quantitative. Adolescence is known as adolescence is someone who grows into an adult or is known as the development of becoming an adult. When they enter adolescence, they should need to get more attention and supervision from their parents. One way is to put them in a good environment. The problem that usually occurs in adolescence is usually promiscuity. The results of this study obtained a correlation coefficient score of 0.403 with a significance level of 0.002 (p<0.5) which show that the hypothesis is accepted, which means that there is a relationship between parental support and sexual behavior trends in adolancents in the north Bekasi.